Práticas de letramentos com memes: uma proposta para as aulas de língua inglesa no ensino médio - Dantas, Rubens Oliveira (2021)
Developing a proposal for literacies with the meme genre in English classes is a somewhat challenging and innovative task. We know that the English language is the world language of the labor market, culture and science. Therefore, it is easy to recognize its usefulness and importance, because the globalized world communicates in English. But there is a relevant aspect in relation to the English language that has been, over the years, loaded with criticism and questions here in Brazil: the school process of teaching and learning the language. Research data related to English learning in Brazil, mentioned in our work, as well as low performance in the classroom and the little interest of learners in language learning, encourage us to reflect on the pedagogical methodologies adopted. Given this premise, for the focus of our research, we take the meme, in particular, as a genre proper to the virtual environment that can boost significant work in English language classes, with a view to promoting literacy and the development of communicative competence of students. For this, we spoke with authors such as Antunes (2001), Paiva (2001) and Rajagopalan (2005; 2011), with regard to teaching and learning languages and Kleiman (2014), Rojo (2009; 2015) and Silva (2016), regarding the approach of issues involving digital genres, especially memes, as an influence for multiliteracies. Regarding the methodological design, this study was characterized as a qualitative research with an action research bias. Thus, we rely on the sequence of procedures suggested by Paiva (2019) and Kemmis and McTaggart (1998) so that, in fact, they meet the needs of following the work developed step by step. We obtained a total of 40 memes produced and posted on the Whatsapp and Facebook group, involving themes that had repercussions in 2020, especially on remote classes, the COVID-19 pandemic and municipal elections. Therefore, the result of this pedagogical literacy intervention with the meme genre showed us the importance of seeing English language classes as a space for the construction of meanings, which interacts and uses the students' daily content. Therefore, being aware of the potential of meanings to which these texts lend themselves, students were able to use the English language in real situations of their daily lives with spontaneity and good humor and to stand before facts and information, as critical citizens, engaged and participatory in society